Assessing pattern of the Pediatric Multisystem Inflammatory Syndrome (PMIS) in children during the COVID-19 pandemic: experience from the emergency department of tertiary care center of a low-middle-income country - Saleem Akhtar; Iqra Anis; Nirdosh Ashok Kumar; Muhammad Tayyab Ihsan; Ahmed Raheem; Surraiya Bano (BMC, 2024)
Abstract Background Pediatric Multisystem Inflammatory Syndrome (PMIS) is a hyperinflammatory condition affecting multiple organs in children, often resembling incomplete Kawasaki Disease during later phases of COVID-19 infection. Data on PMIS in low-middle-income countries, particularly in emergency department settings, is limited. Objectives This prospective observational study at Aga Khan University Hospital, Karachi, aimed to determine the frequency, clinical presentation patterns, and laboratory parameters of children with PMIS visiting the emergency department during the COVID-19 pandemic. Secondary objectives included assessing factors associated with in-hospital mortality. Methods From March 2020 to September 2021, patients meeting World Health Organization PMIS criteria were enrolled. COVID-19 testing included PCR and antibody testing. Data was collected through a questionnaire and analyzed statistically. Results Among 56 PMIS patients (85.7% male, mean age 7.67 ± 4.8 years), respiratory symptoms (70%), neurological symptoms (57%), and gastrointestinal symptoms (54%) were common presentations. Signs included delayed capillary refill time (93%), low-volume pulses (89%), and hypotension (68%). COVID-19 antibodies were positive in the majority (78.6%) while PCR was positive in 18%. Risk factors for mortality included prolonged emergency department stay, and high Ferritin and Lactate Dehydrogenase levels. Conclusion PMIS affects children of all ages. Respiratory and gastrointestinal symptoms are the most frequent presentations. Elevated inflammatory markers, including LDH, Ferritin, D-dimer, and Pro-BNP, correlate with higher mortality risk.